Older Age and High Serum Ferritin Levels Associated With the Risk of Chronic Cytopenia in Hemodialysis Patients - Lee, Yu-Ting; Wang, Wei-Yu; Kuo, Chin-Ho; Lee, Ming-Yang; Lu, Yin-Che; Hsiao, Chih-Yen; Hsu, Yueh-Han; Hung, Peir-Haur (Frontiers in Medicine, 2020)
Leukopenia or thrombocytopenia is sometimes observed in end-stage renal disease (ESRD) patients, but the association between chronic leukopenia or thrombocytopenia and hemodialysis (HD) is still unclear. We aimed to investigate the incidence of chronic leukopenia or thrombocytopenia in patients with ESRD who received HD and to determine the risk factors of this complication. We retrospectively analyzed ESRD patients treated with HD at Ditmanson Medical Foundation Chia-Yi Christian Hospital in 2018. The risk factors for the occurrence of chronic leukopenia and thrombocytopenia were analyzed by Cox regression models. Of the 473 patients in our study cohort, 46 (9.7%) patients had a hematologic abnormality, including 18 patients with chronic leukopenia, 18 with chronic thrombocytopenia, and 10 with pancytopenia. Multivariate analysis revealed that patient age ≥60 years at the initiation of dialysis was a significant predictor for both chronic leukopenia [adjusted hazard ratio (aHR), 2.71; 95% confidence interval (CI), 1.06-6.89] and chronic thrombocytopenia (aHR, 2.83; 95% CI, 1.08–7.35). Chronic liver disease (aHR, 3.31; 95% CI, 1.27–8.61) and serum ferritin levels >800 mg/dl (aHR, 3.29; 95% CI, 1.29–8.39) were risk factors for chronic thrombocytopenia. A trend showed that vitamin D from intravenous supplementation (aHR, 0.13; 95% CI, 0.01–1.16, P = 0.066) and serum phosphorous level (aHR, 0.73; 95% CI, 0.53–1.02, P = 0.068) may be associated with chronic thrombocytopenia. Our study demonstrated that hematological abnormality was a long-term complication of HD. These results reveal that older patients with HD and high serum ferritin levels are at an elevated risk for chronic cytopenia. Healthcare professionals should be aware of this risk when treating HD patients in order to improve their prognosis.